Interventions to curb deforestation and stability in access to land: A comparative study between two land regulation modalities in the Transamazon region, Brazil - Santos, I.V.; Porro, N.M.; Porro R. (International Land Coalition, 2011)
This paper addresses the interaction between the reinforcement of environmental laws and the stability of beneficiary families in agrarian reform settlements, in a context of increasing environmental concerns pressured by climate change. The study compares two modalities of land regulation in the Amazon Settlement Projects (PA) and Sustain-able Development Projects (PDS). The former is a conventional modality, where govern-mental apparatus has not been able to reinforce even general national environmental rules. The latter is a so-called Special Settlement, where environmental concerns were incorporated into the concept of this land regulation instrument and, at least theoretical-ly, rules would be more strictly reinforced. Integrating quantitative and qualitative data, we examine four issues involved in the interactions between stability on the land and reinforcement of environmental laws: forms of accessing land, the legal situation of land property, actual places of residence, and conditions for family farming. Results show that the modality of land regulation per se does not affect the mobility of families from agrarian reform settlements, which remains high under either modality. Evidence from the field elicits how the search for a land without landlords, with conditions to work for oneself, is at the core of why families leave hard-earned reformed plots behind to pursue new opportunities.